1990
DOI: 10.1111/j.1365-2028.1990.tb01156.x
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine residues in fish from Lake Victoria, Kenya

Abstract: SummaryEighty‐two samples of either nile perch fish fat or muscle were collected from the Kenyan region of Lake Victoria for detection of organochlorine residues. Nine organochlorine residues were detected in the following percentages: α‐BHCIHCB‐40%; P‐BHC/HCB‐40%; y‐BHC/HCB/lindane‐4%; aldrin‐9%; dieldrin‐1%; p, p'‐DDE‐73%; p, p'‐DDD‐9%; o, p'‐DDT‐170; and p, p'‐DDT‐11%. All levels of organochlorine residues were below the Extraneous Residue Limit (ERL), apart from just one sample of fish fat which had 4.51 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
7
2
Order By: Relevance
“…The highest mean pesticide residue concentration of 0.062 mg kg -1 of p,p~-DDT, found in a fat sample, was generally low. It was lower than a mean level of 0.15 mg kg-1 of p,pl_DDT found in fish from Lake Victoria (Mitema and Gitau, 1990). The mean residue concentration levels of sum-DDT (0.004 mg kg -1) and heptachlor (0.007 mg kg -1) were far below the United States Food and Drug Administration (FDA) (1982) action limits of 5.0 mg kg -1 and 0.03 mg kg -1, respectively.…”
Section: Discussioncontrasting
confidence: 50%
“…The highest mean pesticide residue concentration of 0.062 mg kg -1 of p,p~-DDT, found in a fat sample, was generally low. It was lower than a mean level of 0.15 mg kg-1 of p,pl_DDT found in fish from Lake Victoria (Mitema and Gitau, 1990). The mean residue concentration levels of sum-DDT (0.004 mg kg -1) and heptachlor (0.007 mg kg -1) were far below the United States Food and Drug Administration (FDA) (1982) action limits of 5.0 mg kg -1 and 0.03 mg kg -1, respectively.…”
Section: Discussioncontrasting
confidence: 50%
“…They reported residues of lindane, aldrin, p,p'-DDT and p,p'-DDE in most of the samples, whereas endosulfan, dieldrin, p,p'-DDT and endrin were either present in low concentration or absent in most samples [29]. Study conducted on the Pesticide residues in Kenyan rivers and lakes have reported high level of α -HCH, β -HCH, lindane, endosulfan, heptachlor, aldrin, heptachlor epoxide, dieldrin, endrin and methoxychlor in soil and water from the sugar belt zone of lake Victoria basin [27,22] In comparison to studies carried out in other countries, Mwevura et al, (2002) reported few organochlorine pesticides residue at lower frequencies p, p'-DDT (25%); p,p'-DDE (37%) during dry season and high frequencies during wet season giving frequencies of p, p'-DDT (81%) p,p'-DDE (100%), dieidrin (100%) and γ-HCH (6%) in samples from the coast area of Dar es Salaam, Tanzania [30].…”
Section: Discussionmentioning
confidence: 95%
“…The main sources of organochlorine pesticide residues in Lake Victoria region are farming and aerial sprays in public health vector control. DDT and aldrin was mainly used in aerial sprays to kill mosquitoes to manage malaria [27]. Dieldrin and aldrin have been used for a long time to control termite in construction industry [22].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the pesticides that have been used extensively for long periods in Uganda are organochlorines (National Environment Action Plan, 1992). The pesticides DDT, the cyclodienes, and lindane were widely used in agriculture, as well as in mosquito and tsetse fly control programs from the 1940s to mid‐1960s (Wandiga, 2001; Mitema and Gitau, 1990; Sserunjogi, 1974). A previous study on OC concentrations in Uganda was conducted on 13 pilot lakes (Sserunjogi, 1974).…”
mentioning
confidence: 99%